Approaches to movement therapy and their relevance to the design of interactive systems to support rehabilitation - Rennick-Egglestone, Stefan (2012)
Stroke is a major cause of physical disability for those that survive it. Traditionally, treatment of disability involves interaction with professional trained in the movement therapies. However, there is a growing body of research into interactive systems that are intended to provide support for rehabilitation, many of which draw on game-like elements to motivate engagement. A promising tactic to consider when designing such systems is the integration of knowledge from the movement therapies, and this paper is intended to provide support for this tactic. It contributes a detailed consideration of the structure of this knowledge within this domain, considers the challenges inherent in incorporating it into effective designs, and describes a conceptual framework which is intended to support this process. These contributions are illustrated in relation to two influential approaches to movement therapy, namely “Bobath” and the “Motor Re-Learning Program”.